SOSIALISASI PEMBUATAN PUPUK ORGANIK CAIR DARI BAHAN LIMBAH ORGANIK DAN TANAMAN SEMAK C.odorata DI KOTA PADANG - Jamilah Jamilah; Sri Mulyani; Ilham Martadona (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Procurement of artificial fertilizers is very limited, in addition to the high price, sometimes the distribution of fertilizer at retail kiosks experiences various obstacles in the smooth distribution. Therefore there must be other efforts in the procurement of liquid organic fertilizers (LOF) that take from raw materials found in nature. The purpose was to socialize the manufacture of C.odora LOF and its application techniques and benefits to plants. This counseling was carried out at the Nanggalo Agricultural Extension Center (BPP) office, Padang City. The activity began with a request from the Nanggalo Agricultural Extension Center, Padang City, to the Faculty of Agriculture for their willingness to provide counseling in their office. In accordance with the agreed schedule, the activities were carried out. In this activity, the team from the Faculty of Agriculture, consisted of 3 group members and was attended by no less than 20 Padang City instructors. On this occasion, the activity began with remarks from the Head of BPP, then a lecture using an LCD projector and a question and answer discussion about the topics discussed and a group photo. The conclusion was that making of LOF has become important at this time because artificial fertilizers are increasingly expensive and limited in availability. Agricultural extension workers have an important role in disseminating this activity to farmer groups in their working areas. Making LOF is also one of the efforts to reduce organic waste that can pollute the environment.